Assessing the impacts of Grain-for-Green Programme on ecosystem services in Jinghe River basin, China. (April 2022) - Xu, Chao; Jiang, Yanan; Su, Zhenhui; Liu, Yujun; Lyu, Jingyu
Highlights: LULC change in Jinghe river basin due to GFGP are analyzed. Three ecosystem services change due to GFGP are assessed based on InVEST models. There are clear tradeoffs and synergies among three ecosystem services due to GFGP. Grasses are better considering trade-offs in water yield and sediment control. Abstract: Land-use/land-cover (LULC) change could have huge impacts on a wide range of ecosystem services, such as the quality, types, processes, temporal, and spatial patterns of ecosystem, leading to dramatic changes in different types of ecosystem services. China has implemented Grain-for-Green Programme (GFGP) to alleviate soil erosion, restore and improve ecosystem services. We selected Jinghe River basin, one of the main GFGP pilot areas in the central part of the Loess Plateau in China as study area. InVEST models were adopted to quantify three of the most important ecosystem services (water yield, sediment control and carbon storage) from 2000 to 2015, during which an important GFGP process happens. Results showed that compared with 2000, the area of farmland decreased by 466 km 2, the area of degraded grassland decreased by 394 km 2, while the area of forestland increased by 339 km 2 (including shrub land) in Jinghe River basin. The average annual water yield and sediment export from 2000 to 2015 is 1.11 × 10 9 m 3 and 9.67 × 10 7 t, which is 36.2% and 60.7% lower than the average of the previous 50 years. Unsurprisingly, carbon storage has increased 5907559.28 mg, about 2.4% more compared to 2000. There are trade-offs between water yield and sediment control as well as carbon storage, and there are synergies between sediment control and carbon storage. Our quantitative assessment has revealed the complex spatial and temporal trade-offs and synergies among competing ecosystem services during the GFGP process. In addition, the results of t-tests in the sub-basin showed that the water yield and sediment control of grassland restoration area and forestland restoration area are better than those of farmland. The water yield of grassland restoration area is better than that of forestland restoration area. But it is difficult to judge the sediment export in forestland restoration area and grassland restoration area. Therefore, considering the trade-offs between water yield and sediment control, grasses are better vegetation type of GFGP compared to trees for the Loess Plateau which has relatively limited precipitation. Our results showed that the control of the erosion by adding vegetation triggers to a diminution of water yield, especially in arid and semi-arid areas. Decision making regards to future GFGP and ecological restoration projects should consider the complex and competing trade-offs and synergies in a wide range of ecosystem services, and optimize the planting structure and scale of vegetation in order to achieve long-term, secure, and sustainable provision of vital ecosystem services.